Identifying key elements of ecological restoration in shallow-buried high-intensity mining area based on obstacle degree model a case study in Huojitu mine - Zhang, Hebing; Zhu, Zhiyong; Wang, Shidong; Zou, Youfeng; Chen, Zhichao; Zhao, Yanling; Chen, Qiuji; Jiao, Yiheng; Li, Yifu; Du, Haoyang (Frontiers in Environmental Science, 2025)
The idea of green mining has attracted much attention over the past decade. Accurate identification of key elements of ecological restoration in mining areas is an important prerequisite for ecosystem restoration and reconstruction and improving the quality of ecological environment. The goal of this study is to develop a five-factor index system for ecological restoration in mining areas, with the Huojitu well serving as a case study of a typical western shallow-buried high-intensity mining area in China. The factors include vegetation cove, soil, ecological landscape, land damage and site condition. An obstacle factor diagnosis model based on the coupling of obstacle degree and Shefold restriction law has been established in this research. This model is used to identify the obstacle factors and analyze the key elements of ecological restoration in the mining area. The key elements of ecological restoration are identified by combining the obstacle degree of each obstacle factor. According to the findings, out of all the areas included in the study, the one pertaining to soil conditions was the biggest at 35.29 km2, or 31.91% of the total, followed by land damage condition (21.25 km2 ∼19.20%), site condition (19.74 km2∼17.84%), vegetation cover (3.34 km2, ∼3.02%), and ecological landscape (31.08 km2∼ 28.03%). Based on the identification results of critical elements in mining area ecological restoration, this study proposes targeted remediation strategies and formulates corresponding site-specific rehabilitation measures to facilitate efficient ecosystem recovery in mining regions. This approach not only advances the practical implementation of ecological restoration technologies but also provides a valuable reference framework for sustainable ecosystem management in post-mining landscapes.